The impact of K-pop on the South Korean economy ("Journal "U". Economy. Management. Finance.", 2024)
It is no secret that over the past two decades, South Korea has risen as a country due to many factors. But most often, when people think about this, they only think about shipbuilding, technology and mechanical engineering. I am sure that Korea was also influenced by another factor - the growing popularity of the K-pop music genre and it's becoming a global phenomenon influencing the whole world. In my research, I highlighted the main points of influence of idols on the Republic of Korea.
Keywords: Korea; BTS; group; K-pop; idol; influence; export; Jungkook